PERSEPSI MASYARAKAT TERHADAP SANDO MONGGOKI’I (Dukun Peramal Benda yang Hilang) DI KELURAHAN KULAHI KECAMATAN WAWOTOBI KABUPATEN KONAWE - Kiki Fitriani; Syamsumarlin Syamsumarlin; La Janu (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2017)
This study aims to determine and to describe the public perception of the sando mongiki'i in finding missing objects using Goodenough's theory of cognition. The method used in this study is the field research method. Data collection uses observation techniques and interviews. While the selection of informants was determined by purposive sampling. The results shows that some of the Tolaki people in Kulahi village perceived sando monggiki'i as a solution in finding lost items, and were considered capable of safeguarding possessions by using amulets, or water that had contained spells. This is motivated by a number of things, including a) the weak role of the legal apparatus in monitoring criminal acts; b) the lack of public understanding of religious values and norms; and c) the habits of the people who have become part of their culture.